A management system based on the balanced scorecard to improve the competitiveness of an industrial sector company located in the district of Chorrillos - Aguilar Cusihuamán, Roberto (2018)
This investigation was based on an analysis of the implementation of the Balanced Scorecard for an industrial sector company. The theoretical foundations were supported by the work of Kaplan and Norton (2008), who indicated that the Balanced Scorecard is a basic management tool that makes it possible to integrate an organization with its vision through strategies that link objectives and indicators. The study population was comprised of all the existing processes within the company. It was found that the implementation of a Management System through the Balanced Scorecard improves the Competitiveness of an industrial sector company located in the district of Chorrillos. For this analysis, Chi-square statistical test was utilized, where p-value is less than 0.005, and for this case, the value was 0.002.